KELUAR DARI KEMISKINAN: STUDI PEMBANGUNAN DAN PEMBERDAYAAN JEMAAT DI DUSUN SIAHARI, KECAMATAN SERAM UTARA TIMUR - George Marthen Likumahwa; John A Titaley; Steve Gaspersz (Program Pascasarjana UKIM, 2020)
The people of Siahari, North East Seram Subdistrict, Kobi, experience poverty problems that can threaten their living. The problem covers various aspects of life, namely education, health, economy, and infrastructure which includes transportation, housing, electricity, and living foods. This research uses qualitative methods with interviews, observation, documentation, and literature study techniques. The results of the study found that the people of Siahari, North East Serobi District of Kobi were at an absolute, relative, and structural level of poverty. In addressing these issues, GPM is called upon to carry out acts of empowerment by referring to the theological foundations within them including the spirituality of ugahari. In addition, the church and the government can also build cooperation to conduct empowerment actions so that the people of Siahari can experience holistic and comprehensive transformation.